2018
DOI: 10.1016/j.arthro.2017.10.042
|View full text |Cite
|
Sign up to set email alerts
|

An In Vivo Prediction of Anisometry and Strain in Anterior Cruciate Ligament Reconstruction – A Combined Magnetic Resonance and Dual Fluoroscopic Imaging Analysis

Abstract: An area of least anisometry was found in the proximal-distal direction just posterior to the intercondylar notch. ACL reconstruction at the isometric and OTT location resulted in nonanatomic graft behavior, which could overconstrain the knee at deeper flexion angles. Tibial location significantly affected graft strains for the anatomic, OTT, and isometric socket location. CLINICAL RELEVANCE: This study improves the knowledge on ACL anisometry and strain and helps surgeons to better understand the consequences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…A recent study highlighted the importance of restoring functional anatomy in ACL reconstruction to achieve normal knee function [ 4 ]. Isometric placement of the graft resulted in nonanatomical graft behaviour, which can overconstrain the knee at larger flexion angles [ 7 ]. Therefore, biomechanical considerations of grafts in ACL reconstruction are as important as isometric considerations are.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study highlighted the importance of restoring functional anatomy in ACL reconstruction to achieve normal knee function [ 4 ]. Isometric placement of the graft resulted in nonanatomical graft behaviour, which can overconstrain the knee at larger flexion angles [ 7 ]. Therefore, biomechanical considerations of grafts in ACL reconstruction are as important as isometric considerations are.…”
Section: Discussionmentioning
confidence: 99%
“…This approach is limited to ex vivo applications. Because forces and stresses are directly related to strains, investigators have measured ligament displacements and calculated strain patterns to gain an understanding of the in vivo biomechanics of ACL grafts recently [ 7 ]. The combined magnetic resonance (MR) and dual fluoroscopic imaging analysis is useful for in vivo applications.…”
Section: Introductionmentioning
confidence: 99%
“…Laboureau [ 15 ] found the femoral isometric point is located anterior to the anatomic footprint region, at approximately 60% of the anteroposterior length of the condyle when measured on a line parallel to the Blumensaat's line. Recent computerized studies [ 17 , 18 ] have partially supported this viewpoint showing that an isometric region in the femoral sagittal condyle and the anterior non-anatomical point have better isometry compared to the anatomical point whilst individual differences exist. These studies focused more on the femoral tunnel position rather than the tibial position [ 8 , 11 ] and demonstrate that the femoral point option is more effective to the isometry of ACLR.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies [ 7 , 8 , 12 , 13 ] have reported the anterior region of the tibial ACL footprint as the most isometric tibial tunnel position rather than the centric or posterior regions when matched with the anatomical femoral tunnel position. Other studies have focused on an “over the top” femoral tunnel position, however, a more posterior tibial tunnel position is recommended from the isometry [ 17 , 18 ] standpoint using the traditional transtibial technique.…”
Section: Introductionmentioning
confidence: 99%
“…1 As previous research has demonstrated, these goals are best achieved using anatomic ACL reconstruction. 2 In the article titled "An In Vivo Prediction of Anisometry and Strain in Anterior Cruciate Ligament ReconstructiondA Combined Magnetic Resonance and Dual Fluoroscopic Image Analysis," 3 Kernkamp, Varady, Li, Tsai, Asnis, van Arkel, Nelissen, Gill, Van de Velde, and Li used dual fluoroscopy and magnetic resonance imaging to precisely track tibiofemoral motion during step-up and sit-to-stand motions in 18 healthy individuals. These tibiofemoral kinematics were used as input to a computer simulation to predict the strain in the ACL at 144 theoretical attachment sites on the femur and 3 theoretical attachment sites on the tibia.…”
mentioning
confidence: 99%